Identifikasi Sumber Ketahanan Aksesi Plasma Nutfah Kedelai untuk Ulat Grayak Spodoptera litura F. - Suharsono Suharsono; M. Muchlish Adie (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2010)
The importantaspect of development of resistant plant to insect pest is sourceof resistance. Study the resistance of 14 advance soybeanbreeding lines to common cutworm Spodoptera litura F. wasconducted at the Laboratory of Crop Protection, IndonesianLegumes and Tuber Crops Research Institute (ILETRI)Malang in February-September, 2006. Leaf damage and larvaldevelopment on resistant genotypes was recorded to measurethe level of resistance. It was found that the susceptibility ofsoybeans to the common cutworm significantly varied amongthe breeding lines. The leaf damage of IAC-100, IAC 80-596-2, and W/80-2-4-20 from larval feeding were 17.67, 18.52, and23.70% respectively lower than Wilis variety with 35.57% ofleaf damage. These breeding lines consistently possess samelevel of resistance to S. litura. In addition, the resistantbreeding lines affect on biological aspects i.e. prolongedduration of larval stage, reduced larval and pupae gain weight,and cause significant larval mortality compared with Wilisvariety. The study suggested that IAC-100, IAC 80-596-2, andW/80-2-4-20 could be used as a source of resistance for S.litura in breeding program.